Novel Biomarkers for Contrast-Induced Acute Kidney Injury. (29th May 2014) - Briguori, Carlo; Quintavalle, Cristina; Donnarumma, Elvira; Condorelli, Gerolama
Abstract : Biomarkers of acute kidney injury (AKI) may be classified in 2 groups: (1) those representing changes in renal function (e.g., serum creatinine or cystatin C and urine flow rate) and (2) those reflecting kidney damage (e.g., kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), interleukin-18, etc.). According to these 2 fundamental criteria, 4 subgroups have been proposed: (1) no marker change; (2) damage alone; (3) functional change alone; and (4) combined damage and functional change. Therefore, a new category of patients with "subclinical AKI" (that is, an increase in damage markers alone without simultaneous loss of kidney function) has been identified. This condition has been associated with higher risk of adverse outcomes (including renal replacement therapy and mortality) at followup. The ability to measure these physiological variables may lead to identification of patients at risk for AKI and early diagnosis of AKI and may lead to variables, which may inform therapeutic decisions.